Epidemiology of Constipation in Elderly People in Parts of China: A Multicenter Study - Du, Xiaoshan; Liu, Shuai; Jia, Peifei; Wang, Xiaodan; Gan, Jinghuan; Hu, Wenzheng; Zhu, Han; Song, Yehua; Niu, Jianping; Ji, Yong (Frontiers in Public Health, 2022)
Purpose To investigate the epidemiological characteristics of constipation in people aged 65 years and older in several regions of China. Patients and Methods A cross-sectional study based on a cluster sampling design was conducted in four cities of China: Tianjin, Xiamen, Cangzhou and Harbin. A total of 5,222 cases (age ≥ 65 years) were recruited, and the survey was conducted via centralized and household questionnaires that included the following: basic demographic characteristics such as sex, age, education, marital status, living status and occupation; social activities; duration of sleep at night; duration of menstruation and delivery times (in females); and if the participant had constipation symptoms, the severity of constipation. Constipation was diagnosed according to the Rome IV criteria. Results Of the 5,222 participants, 919 were diagnosed with constipation. The prevalence of constipation was 17.60% in elderly people ≥65 years old. Prevalence increased with age and was significantly higher in females than males (P < 0.05). Prevalence was lower in the manual compared to the non-manual worker group, and significantly increased with decreasing duration of night sleep (P < 0.05). Older age, female sex and shorter sleep duration at night were risk factors for constipation in elderly people. Conclusion The prevalence of constipation in the elderly people in four cities of China was 17.60%, and was significantly affected by age, sex and sleep duration at night.